2018
DOI: 10.7150/jca.24253
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus 16 E7 oncoprotein alters the expression profiles of circular RNAs in Caski cells

Abstract: Cervical cancer is one of the most common cancer in female worldwide. The expression of high-risk human papillomavirus E7 oncogene is necessary for the maintenance of malignant phenotypes and transformation. Accumulating studies of this protein has been explored in cervical cancer, however, there are fewer studies on how E7 expression affects the expression of global circular RNA. CircRNA, a promising biomarker and even therapeutic target, has become a star molecular in research after miRNA and long non-coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…High-risk subtypes (16 and 18) of human papillomavirus (HPV) are well established as the causative agents responsible for CC [ 69 ]. Massive studies have shown that a large number of circRNAs were differentially expressed in CC tissues compared with adjacent normal cervical tissues, and play oncogenic or tumor-suppressive roles in the initiation and progression of CC [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. All of the circRNAs that are abnormally expressed in CC are summarized in Table 1 , and their functions in CC are shown in Figure 3 .…”
Section: The Expression Functions and Mechanisms Of Circrnas In Gmentioning
confidence: 99%
“…High-risk subtypes (16 and 18) of human papillomavirus (HPV) are well established as the causative agents responsible for CC [ 69 ]. Massive studies have shown that a large number of circRNAs were differentially expressed in CC tissues compared with adjacent normal cervical tissues, and play oncogenic or tumor-suppressive roles in the initiation and progression of CC [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. All of the circRNAs that are abnormally expressed in CC are summarized in Table 1 , and their functions in CC are shown in Figure 3 .…”
Section: The Expression Functions and Mechanisms Of Circrnas In Gmentioning
confidence: 99%
“…MRNA levels of P-gp and GSTP were obviously repressed after downregulation of circ-PVT1 in paclitaxel-resistant gastric cancer cells 157 . Moreover, high-throughout microarray-based circRNA profiling revealed that 526 circRNAs were dysregulated in cervical cancer cells, and bioinformatic analyses indicated that these circRNAs participated mainly in GSH metabolism 158 . However, associated miRNAs and downstream factors were not screened.…”
Section: Introductionmentioning
confidence: 99%
“…2 Some studies have shown the ectopic expression of noncoding RNAs such as circRNAs and miRNAs in CC. Recent studies have revealed the ectopically expressed circRNA profiles associated with HPV 16 infection 26 and radioresistance. 27 CircRNAs with dysregulated expression are found to be associated with CC carcinogenesis and progression through the regulation of cell migration, invasion, metastasis and recurrence in CC.…”
Section: Discussionmentioning
confidence: 99%